SECOND TAKEOFF : Strategies For Malaysia's Economic Resurgence - Liew, Chin Tong (World Scientific, 2025)
"The Malaysian economy is at a crossroads amid global and regional shifts in geopolitics. Malaysia is in a prime position to benefit from the renewed appetite for investment into the region. If Malaysia gets its priorities right, this could be the beginning of the country's next economic takeoff. An updated collection of Chin Tong's writings on economics, society and governance over the years, this book provides policy suggestions to catapult Malaysia's development to the league of high-income nations amid ongoing geopolitical trends. Central to his thesis is the need for Malaysia to create a middle-class society, in which the economic structure supports the creation of dignified jobs with decent pay for all Malaysians. Chin Tong is no stranger to the centrality of jobs in the pursuit of a good life, having grown up selling lottery tickets alongside his mother and waiting tables as a teenager to make ends meet for his working-class family. His eventual experience as a Member of Parliament for over a decade and a Deputy Minister in two different administrations further confirmed his beliefs that good jobs are the crucial missing component in Malaysia's growth engine. In this book, Chin Tong takes us on a whirlwind tour of Malaysia's socio-economic history, what went wrong after the first growth miracle of 1988-1997 and how to make things right this time around. Ultimately, the book tells the story of how to fulfil Chin Tong's undying wish for a Malaysia where everyone has a chance to live a good life with a good job under a responsible and kind state"--